Tolerance to total dissolved gas supersaturation in Atlantic salmon, brown trout, rainbow trout, and European minnow - Trond Einar Isaksen; Ulrich Pulg; Robert J. Lennox; Sebastian F. Stranzl; Einar Bye-Ingebrigtsen; Reidar Handegård; Gaute Velle (PLoS ONE, 2026)
Gas bubble disease is a major concern for aquatic animals in rivers downstream of hydroelectric power plants, where water can become supersaturated with dissolved gas. While the disease is well documented in Pacific salmonids ( Oncorhynchus spp.), its effects on juvenile Atlantic salmonids ( Salmo spp.) and non-salmonid fish in Europe are limited or unknown. To assess the impacts of gas bubble disease in Norwegian rivers, experimental trials exposed juvenile Atlantic salmonids ( Salmo salar and Salmo trutta ) and adult European minnows ( Phoxinus phoxinus ) to dissolved gas supersaturation ranging from 100% (normal) to 120%. A total of 1 440 fish were included in the trials, comprising Atlantic salmon larvae (alevin, n = 250; fry, n = 250), salmon parr ( S. salar , n = 325), brown trout parr ( S. trutta , n = 340), and minnow ( n = 250). The study also included a repeated trial with salmon parr ( n = 25) and a reference trial with rainbow trout parr ( Oncorhynchus mykiss , n = 25). Results showed both intra- and interspecific differences in tolerance to total dissolved gas supersaturation. Atlantic salmon larvae (alevins and fry) and European minnows tolerated higher supersaturation, showing low mortality and only subacute gas bubble disease pathogenesis at levels up to 120% total dissolved gas supersaturation. Acute disease occurred only in larger salmonid parr at 115–120%, with gas emboli in gills and subcutaneous emphysema appearing within 1–6 hours. At 120%, mortality rates were significantly higher (p < 0.003) in salmon and brown trout parr compared to rainbow trout parr, ranging from 1.2–7.5 dead or moribund fish per hour (LT 50 in 4–15 hours) versus 0.5 per hour in rainbow trout (LT 50 in 25 hours). Lethal time for 50% mortality (LT 50 ) was used as a criterion for terminating the trials. Recovery tests were conducted only on salmon larvae and brown trout in our study, and the results indicated partial recovery following exposure to sublethal gas supersaturation. These findings define lethal and sublethal thresholds of gas supersaturation for multiple species and life stages, highlight lower mortality rate in rainbow trout compared to Atlantic salmonids, and present the first documented effects on the non-salmonid European minnow (Cypriniformes). The results provide a basis for assessing potential ecological impacts of total dissolved gas supersaturation in Norwegian and European rivers.